Modeling of Frequency Dependent Parameters in Time Domain High Frequency Transformer Simulations. (2017) - Smajic, J.; Bucher, M.; Franz, T.; Cranganu-Cretu, B.; Shoory, A.; Tepper, J.
Abstract: Modeling details of frequency dependent parameters and a method for taking those into account in time domain high frequency (HF) transformer simulations are presented. Frequency dependent turn resistance and core losses are considered. The suggested method is general and thus not limited only to the considered frequency dependent parameters. Frequency dependent turn resistance and core losses are obtained by performing frequency domain (FD) finite element method (FEM) simulations. The obtained frequency dependences are approximated by a set of functions with existing Inverse Fourier Transform (IFT) and used in convolution integrals of the time domain model of a transformer winding system. The obtained simulation results are verified by comparison against measurements.